Optimalisasi Penerapan Keselamatan dan Kesehatan Kerja di Laboratorium - Nyayu Nurul Husna; Naomi Tosani; Neny Afridayanti (Pusat Riset dan Inovasi Nasional, 2022)
Working in a laboratory is inextricably linked to the various potential hazards. The purpose of this study was to determine the extent of the application of occupational safety and health in laboratories and to find out the obstacles to the application of OHS in Faculty of Agriculture, Sriwijaya University. This research is a descriptive study with a qualitative approach and was conducted in eight laboratories in the Faculty of Agriculture, namely the Agricultural Cultivation Laboratory, Agricultural Product Technology Laboratory, Plant Pest and Disease Laboratory, Soil Laboratory, Aquaculture Laboratory, Agricultural Product Technology Laboratory, Animal Nutrition and Feed Laboratory. The data was collected by means of interview, observation and documentation. Based on the results of the research, it can be concluded that the overall percentage of questionnaire results is 54% who answered yes and 46% answered no. This means that most of the Agricultural Faculty laboratories have not implemented OHS properly.